OVERVIEW OF PRIMIGRAVIDA PREGNANT WOMEN'S KNOWLEDGE ABOUT DANGEROUS SIGNS OF PREGNANCY IN THE WORK AREA BAUBAU CITY MEO-MEO HEALTH CENTER - Wulandari, Wulandari; Salim, Ika Lestari; Lestari, Wa Ode Sriwati (Jurnal Kesehatan dan Teknologi, 2024)
Pregnancy danger signs are signs that indicate danger that may occur during pregnancy or the antenatal period. And if it is not detected early it can threaten the safety of the mother and fetus. The aim of this research is to determine the description of knowledge of primigravida pregnant women regarding the danger signs of pregnancy at the Meo-Meo health center in Baubau City in 2023. This type of research uses a descriptive method with a cross-sectional design, the population in this study is primigravida pregnant women with a sample of 30 people. The sampling technique is total sampling. The research instrument used a questionnaire and data was analyzed using SPPS version 21.0. The results of this study show that from 30 respondents, based on the knowledge of primigravida pregnant women about the danger signs of pregnancy, it was found that most of the mothers' knowledge was quite knowledgeable, namely 13 respondents with a percentage of 43.3% with good knowledge, namely 12 respondents, 40.0% and less knowledgeable, namely 5 respondents with a percentage of 16.7%.